Research on multi-channel routing threats and defense for cognitive ad hoc network - Jing-yu FENG; Xu DU; Hong-gang WANG; Wen-hua HUANG (Tongxin xuebao)
In the environment of scarce spectrum resources,cognitive ad hoc network which is independent with infrastruc-ture and fixed spectrum allocation policy,has been also developed quickly.Due to the characteristic of multi-channel routing,cognitive ad hoc network is commonly perceived as an environment offering both opportunities and threats.To further un-derstand the multi-channel routing threats,the current research situation and development trend,the types of threats were analyzed in terms of the node routing and the multi-channel selection,and several typical security methods were concluded.Meanwhile,the most important solution to keep the security of cognitive radio network was found to build trust relationship among cognitive users.Trust management was just the basic technology to solve the security problems of multi-channel routing.Finally,the current problems of related works and research trends in this area were discussed.